Oil discovery and macroeconomic management: The recent Ghanaian experience - Mahamudu Bawumia; Håvard Halland (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
This paper analyses the evolution of fiscal and monetary variables in Ghana, from the discovery of oil in 2007 through to 2014. It documents the deterioration of fiscal and monetary discipline over this period, which resulted in a rebound of debt, a deterioration of the external balance, and a decrease in public investment. The paper goes on to analyse the potential causes of this deterioration, including the political economy context, and the fiscal and monetary institutional framework. The suggested causes include the politics of Ghana's dominant two-party system. Finally, the paper discusses what Ghana could have done differently to avoid the various damaging effects associated with the oil discovery. It does not aim to provide specific fiscal policy recommendations for Ghana, but rather to give an empirical account of Ghana's experience that may be useful for other countries that discover oil.
Keywords: 330; Ghana; macroeconomic policy; oil; fiscal consolidation